Black-White gap in self-employment in the US: Do cohort and within race differences exist? - Ruth Uwaifo Oyelere; Willie Belton (Institute for the Study of Labor (IZA), 2010)
In this paper we ask three questions: First, is there evidence of a Black-White gap in self-employment between 1994-2002 and could the inclusion of the White immigrant population be driving this result? Second, do within race differences in self-employment exist among the U.S. born? Finally, do cohort differences in the Black-White self-employment gap exist among the U.S. born? These questions are based on some of the regression findings in our earlier paper focused on the role of information and institutions in understanding the Black-White gap in self-employment. We find that the Black-White self-employment gap is not driven by the existence of White immigrants in the data set. In addition, we find that within race and cohort differences exist in the Black-White self-employment gap. A subgroup of U.S. born African-Americans have a self-employment probability that is identical to that of U.S. born White-Americans. In addition, younger cohorts of African-Americans have a much smaller self-employment gap than do older African-Americans.
Keywords: J10; J11; J15; L26; 330; self-employment; disparities; black-white gap; Selbstständige; Farbige Bevölkerung; Weiße; Kohortenanalyse; USA